Is there potential for therapeutic drug monitoring of biologic agents in rheumatoid arthritis?. (18th January 2017) - Bastida, Carla; Ruíz, Virginia; Pascal, Mariona; Yagüe, Jordi; Sanmartí, Raimon; Soy, Dolors
Abstract : The use of biologics has significantly changed the management of rheumatoid arthritis over the last decade, becoming the cornerstone treatment for many patients. The current therapeutic arsenal consists of just under 10 biologic agents, with four different mechanisms of action. Several studies have demonstrated a large interindividual pharmacokinetic variability, which translates to unpredictability in clinical response among individuals. The present review focuses on the pharmacokinetics and pharmacodynamics of biologic agents approved for rheumatoid arthritis. The literature relating to their concentration–effect relationship and the use of pharmacokinetic–pharmacodynamic modelling to optimize drug regimens is analysed. Due to the scarcity and complexity of these studies, the current dosing strategy is based on clinical indexes/aspects. In general, dose individualization for biologics should be implemented increasingly in clinical practice as there is a direct benefit for treated rheumatoid arthritis patients. Moreover, there is an indirect benefit in terms of cost‐effectiveness.